2022
DOI: 10.1186/s13063-022-06276-y
|View full text |Cite
|
Sign up to set email alerts
|

Single vs. double intracoronary injection of mesenchymal stromal cell after acute myocardial infarction: the study protocol from a randomized clinical trial: BOOSTER-TAHA7 trial

Abstract: Background Meta-analysis from previous studies have shown that treatment with mesenchymal stromal cell (MCSs) may increase the left ventricular ejection fraction (LVEF) after acute myocardial infarction (AMI) by 3.84%, and the effect is greater in those who are not aged and have developed a reduced LVEF. However, it seems that MSC transplantation does its effect through an indirect paracrine effect, and direct differentiation to the cardiomyocytes does not occur. Therefore, it can be hypothesiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…An independent Data and Safety and Monitoring Board (DSMB) monitored patient safety during the study. In-depth details regarding the study protocol are available in a previous publication [ 24 ] (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An independent Data and Safety and Monitoring Board (DSMB) monitored patient safety during the study. In-depth details regarding the study protocol are available in a previous publication [ 24 ] (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Qualification was performed according to GMP grade qualification protocols, and viability was assessed with methylene blue before transplantation. More details are provided on the published protocol of study [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is while stem-cell-based therapies go one step further and attempt to reverse the damage through the provision of fresh, functional cells (22). While early studies on this topic were not very promising ( 9), later meta-analyses showed that this therapy might be effective in certain populations (23,25,26,27,28,29,30). Hence, in the present study, we selected patients below 65 with an echocardiographic LVEF <40%, yielding promising results.…”
Section: Discussionmentioning
confidence: 99%
“…This study had some limitations. Firstly, while we originally planned to conduct a sham procedure as a placebo treatment for the control group (25), this did not receive ethical clearance from our institute.…”
Section: Discussionmentioning
confidence: 99%
“…As a pilot phase one study, it is not possible to draw a solid conclusion regarding the efficacy of UMSC01 transplantation. Nevertheless, another randomized clinical trial is ongoing, which compares single with double IC infusion of umbilical cord-derived Wharton’s jelly MSCs in patients with AMI ( 33 ). The result may provide better understanding of the effect of repeated transplantation of this cell type on myocardial function (LVEF).…”
Section: Discussionmentioning
confidence: 99%